أثر بناء الكفاءات المحورية في تحسين أداء المؤسسات دراسة حالة مؤسسة البسكرية للاسمنت - جودي, أمينة; منصوري, كمال (Recherches économiques et managériales; Vol. 12 No 02 (2018): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2020)
: هدفت هذه الدراسة إلى التعرف على أثر بناء الكفاءات المحورية في تحسين أداء مؤسسة البسكرية للاسمنت من وجهة نظر عامليها. ولتحقيق ذلك تم استخدام استبانة كأداة رئيسية في جمع البيانات المتعلقة بالجانب الميداني، حيث وزعت على عينة بلغت(42 إطار)، وقد توصلت هذه الدراسة إلى استنتاجات عدة أهمها وجود أثر ذو دلالة إحصائية  لبناء الكفاءات المحورية على مستوى تحسين أداء المؤسسة محل الدراسة، حيث فسر متغير بناء الكفاءات المحورية ما نسبته (50.7%) من التباين الحاصل في مستوى تحسين الأداء بالمؤسسة محل الدراسة. الكلمات المفتاحية : بناء الكفاءات المحورية، تحسين الأداء، المؤسسة البسكرية للاسمنت.  Abstract: This study aimed to identify the impact of core competencies building in improving the performance   Albeskriah Cement Company from the point of view of their employees. To achieve that, it has been used a questionnaire as a key tool in data collection related to the field  side , where given out on a sample consisted of (42 workers).       The study reached to a set of results, the most important of them including:  there is significant statistical impact for core competencies building in improving the performance of the Company. where core competencies building  explained its percentage (50.7%) of the variance in the level in improving the performance of the Company of study. Key words : Core Competencies Building, Improving The Performance, Albeskriah Cement Company.